Romanian Inventory of Depression and Anxiety Symptoms (IDAS-II) - Ligiana Mihaela Petre; Delia Alexandra Gheorghe; David Watson; Laurentiu Mitrofan (Frontiers in Psychology, 2023)
BackgroundThe Inventory of Depression and Anxiety Symptoms (IDAS-II) is a self-report measure comprising 99 items divided into 18 non-overlapping scales that allows for a dimensional assessment of depression, anxiety, and bipolar symptoms. The IDAS-II is currently available in English, Turkish, Spanish, German, and Swedish. This study’s major goal was to adapt and validate the IDAS-II to the Romanian population.MethodParticipants from a community sample (N = 1,072) completed the IDAS-II (Romanian version) and additional measures assessing depression and anxiety disorders.ResultsItem-level factor analyses validated the unidimensionality of the scales, and internal consistency results indicated that most symptom scales had satisfactory alpha coefficient values. Based on previous structural analyses, a confirmatory factor analysis (CFA) on the IDAS-II scales confirmed a three-component model of “Distress,” “Obsessions/Fear,” and “Positive Mood.” Convergent and discriminant validity were established by correlational analyses with other symptom measures.LimitationsThis study was conducted using a sample from the general population and several of the employed measures have limitations. Specifically, the current study was unable to employ Romanian versions of the gold-standard instruments that assess well-being, obsessive–compulsive disorder, and claustrophobia.ConclusionThe IDAS-II (Romanian version) is the first clinical measure to assess internalizing dimensions of the Hierarchical Taxonomy of Psychopathology (HiTOP) model that is available for the Romanian population.